The Effect of Reproductive Health Education on Knowledge and Attitudes of Adolescent About Premarital Sex in Private Vocational School Surabaya - Puji Hastuti; Yurista Prahesti; Esti Yunitasari (Pediomaternal Nursing Journal, 2021)
Introduction: Adolescence is a period of storms and stress; health problems that occur in adolescents are related to risky behavior, namely smoking, drinking alcohol, abuse of illegal drugs and having premarital sexual relations. The research objective was to determine the effect of reproductive health education on adolescent knowledge and attitudes about premarital sex.Methods: The research design used a quasi-experimental. The study population totalled 356 students. The sampling technique uses non-probability sampling: purposive sampling. A sample size of 188 respondents was obtained—reproductive health education implemented by video and leaflet. Data analysis used the Wilcoxon and Mann Whitney tests with a significant level of 0.05.Results: The results showed that in the video group, the knowledge level was p=0.000, and the attitude was p=0.000. The leaflet group showed a level of knowledge of p=0.000 and an attitude of p=0.000. The difference between the two groups was tested by using the Mann Whitney test. It was found that there was no difference in the effect of the video and leaflet methods on knowledge of p=0.219 and attitudes of p=0.469.Conclusion: Leaflets are effective for health education because they can be read individually and contain topics about premarital sex, which are more personal. The school must provide integrated sexual education with formal lessons that use many methods to increase students’ knowledge.